RELEVANSI FILSAFAT PERENIALISME DALAM MEMBENTUK KARAKTER DAN KECERDASAN INTELEKTUAL PESERTA DIDIK DI ERA MODERN - Ziyadah El fadllilah; Abdul Khobir; Fina Nikmatul Kamelia; Neza Dwi Nasyfa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the relevance of the Perennialism educational philosophy in character development for students in the rapidly changing digital era. Perennialism is based on timeless universal values ​​such as honesty, responsibility, wisdom, and justice, which, according to Taufik Nurrochman (2023), are the primary foundation for developing moral character. Findings by Suharyanto H. Soro (2024) indicate that integrating these values ​​through habituation, teacher role models, and spiritual strengthening can increase students' moral resilience. Other studies, such as those by Afiyah (2020) and Liviani (2023), confirm that the application of noble values ​​through learning, religious environments, and social practices has a significant impact on character development. Amidst the challenges of the digital era, such as the flood of information, the influence of social media, and the ethical crisis, Perennialism is seen as an approach capable of restoring the moral orientation of education. This approach offers a combination of intellectual acuity, moral discipline, and spiritual depth, as explained by Ummi Puji Astutik (2023). Thus, the application of Perennialism in education not only prepares students academically but also shapes them into complete human beings capable of adhering to eternal values ​​in the face of modern dynamics.